Chlorin content, magnetic susceptibility, and lightness records of sediment core LV53-27 (Sea of Japan, 2010) - Sergey A Gorbarenko; Xuefa Shi; Aleksandr A Bosin; Yanguang Liu; Yuriy P Vasilenko; Elena A Yanchenko; Ivan S Kirichenko; Igor Utkin; Antonina V Artemova; Galina Y Malakhova (PANGAEA, 2022)
Sediment core LV53-27 (41° 54' N, 132° 33' E) was retrieved in the northwestern Sea of Japan (Pervenets Seamount) at 1698 m depth during a joint Russian-Chinese expedition LV53 on RV “Akademik M.A. Lavrentyev” in 2010-11-10T23:39:00. The 757-cm long core was characterized by clay/silty clay sediments with alternating dark and light layers. in order to investigate millenial-scale climate changes with ultra-high resolution digital image of this sediment core was processed. Sediment core LV53-27 recovered about 120 kyr according to age model (Gorbarenko et al., submitted to Global and Planetary Changes). Age model was based on correlation of magnetic susceptibility, chlorin content and lightness records with similar records of well-dated sediment core MD01-2407. The magnetic susceptibility (MS) of the sediments was measured in cube samples throughout the core at 2-cm intervals using an AGICO Kappabridge MFK1-FA. These measurements were performed at the Laboratory of Cenozoic Geology and Paleomagnetism of the North-East Interdisciplinary Scientific Research Institute in Magadan, Russia. Data presented as natural logarithm of units SI (International System of Units) Chlorin content was measured with pretreatment procedures and analytical reagents, as proposed by Harris et al. (1996), using a Shimadzu UV-1650PC spectrophotometer at 1 cm resolution. Color lightness (CL) of the sediments was measured using the original photocolorimeter based on a Canon 50D digital camera. One-meter core sections with 14 cm diameter were split into two halves, while performing surface smoothing. Two flash units with soft boxes were used for creating an even and diffused illumination of the sediment surface. Camera shooting was performed with the following settings: ISO 100, 1/100 extquotesingle extquotesingle exposure, and 8.0 focal ratio. Every image covered approximately 40 cm of the core section with approximately 11 pixels per 1 mm stratigraphic resolution. The X-rite Color Checker was used for calibrating the white balance of each image. Digital images were processed with the RTImageProc software for calculating the CL data from black (0) to white (255) with 1-pixel resolution and averaged with 1 mm step. Need to note that the width of the analyzed window of each image (80 mm) in the studied core allow to significantly reduce the possible effect of the sediment bioturbation by organisms several millimeters in diameter.